On the degradation of (micro)plastics: Degradation methods, influencing factors, environmental impacts - Liu, Lingchen; Xu, Mingjie; Ye, Yuheng; Zhang, Bin (The Science of the total environment, 2022)
Plastics and microplastics are difficult to degrade in the natural environment due to their hydrophobicity, the presence of stable covalent bonds and functional groups that are not susceptible to attack. In nature, microplastics are more likely to attract other substances due to their large specific surface area, which further prevents degradation from occurring. Some of these substances are toxic and harmful, and can be spread to various organisms through the food chain along with the microplastics to cause harm to them. Degradation is an effective way to eliminate plastic pollution, and a comprehensive understanding of the methods and mechanisms of plastic degradation is necessary, because it is the result of synergistic effects of several degradation methods, both in nature and in consideration of future engineering applications. The authors firstly summarize the degradation methods of (micro)plastics; secondly, review the influence of intrinsic properties and environmental factors during the degradation process; finally, discuss the environmental impact of the degradation products of (micro)plastics. It is evident that the degradation of (micro)plastics still has many challenges to overcome, and there are no mature and effective methods that can be applied in engineering practice or widely used in nature. Therefore, there is an urgent need for research on the degradation of (micro)plastics. [Display omitted] •An overview of the degradation methods and influencing factors of (micro)plastics.•The synergistic effect is the key to the degradation of (micro)plastics.•The synergistic effect between degradation methods is not sufficiently studied.•The synergistic effect between factors affecting degradation need more studied.•The impact of microplastic degradation products has been poorly studied.